Phytochemical Characterization of the Chloroform Extract of Foeniculum vulgare Mill. Leaves with Implications for Antiparasitic Agent Development - Ihtiaringtyas, Suci; Sari, Octavia Permata; Susiawan, Lieza Dwianasari; Firinda, Rizma Haidif; Amalia, Ary Nahdiyani; Fuady, Rhovee Ilmiawan (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
The development of antiparasitic agents derived from natural products continues to receive considerable attention due to increasing resistance and limitations of conventional therapies. This study aimed to examine the phytochemical profile of the chloroform extract of fennel leaves (F. vulgare Mill.) as a basis for antiparasitic agent development. The extract was obtained using a maceration method and analyzed using thin layer chromatography. Qualitative analysis was conducted based on the observation of visible spots after spraying with appropriate visualization reagents, while supporting analysis was performed based on the calculation of retention factor values for the detected spots. The results revealed the presence of several major groups of secondary metabolites, including flavonoids, terpenoids, alkaloids, and phenolic compounds, as indicated by specific color changes and retention factor values. The diversity of these metabolites suggests the possible involvement of multiple biochemical pathways related to antiparasitic mechanisms. Overall, the phytochemical profile of the chloroform extract of fennel leaves provides important preliminary data to support further research on natural product–based antiparasitic agents.